Konsep dan Filosofi Pemidanaan Dalam Undang-Undang Nomor 12 Tahun 2022 Tentang Tindak Pidana Kekerasan Seksual - Febri Ardiyanto; Ari Wibowo (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
This research aims to determine The Concept and Philosophy of Penalization in Law Number 12 of 2022 on Sexual Violence. Doing this research because sexual violence crimes are a type of offense whose recovery cannot be restored to its original state, thus requiring legal regulations that can fulfill the objectives of the law, namely legal certainty and justice, while also aligning with the concept of penal goals. This research used an normative method by statuta approach and used qualitative description analysis techniques. The results of this study include the concept of penalization in Law Number 12 of 2022 on Sexual Violence Crimes, which adheres to the relative theory with penal sanctions in the form of imprisonment and/or fines formulated alternatively-cumulatively, as well as its philosophy of penalization, namely to ensure that offenders can reintegrate into society and to protect society by promoting order. Although Law Number 12 of 2022 on Sexual Violence Crimes has provided for penal sanctions against sexual violence offenders, the minimum limit for imposing a criminal sentence is still not stipulated in the regulation. It should be provided to allow judges to impose lenient sanctions on perpetrators, given that sexual violence crimes are serious offenses.